Evaluation of the Characteristic Changes of Lightweight Bricks after Immersion - Pertiwi, Nurlita; Taufieq, Nur Anny Suryaningsih; Dirawan, Gufran Darma (Universitas Negeri Makassar, 2025)
Abstract. This study evaluates the effect of immersion duration and water acidity on the compressive strength and porosity of autoclaved lightweight concrete (ALC) bricks. The experimental work was conducted by immersing samples in both normal and acidic water for 7, 14, and 28 days. A total of 260 samples were tested, including 140 specimens for compressive strength and 120 for porosity analysis. Normal water had a pH of 6.5–8.5, while acidic water was adjusted to a pH of 4–5 using nitric acid. The results show a consistent decline in compressive strength with increasing immersion time. The average compressive strength decreased from 2.87 N/mm² (without immersed) to 1.30 N/mm² after 28 days of immersion in normal water, and to 0.40 N/mm² after immersion in acidic water for the same period. Correspondingly, the porosity increased from 18.05% to 32.08% under normal conditions and from 24.24% to 41.04% in acidic conditions. These findings indicate that immersion, particularly in acidic environments, accelerates the degradation of lightweight bricks through calcium leaching, dissolution of cementitious compounds, and pore structure expansion. The study concludes that the durability of lightweight bricks is highly dependent on environmental exposure. Acidic water immersion causes severe chemical and physical damage, reducing both strength and cohesion. Protective surface treatments and improved mix design are therefore recommended to enhance the resistance of lightweight bricks against water and acid-induced deterioration. Keywords: lightweight brick, compressive strength, porosity, immersion, acid attack, durability